2012
DOI: 10.1007/s11695-012-0635-y
|View full text |Cite
|
Sign up to set email alerts
|

Transgastric Endoscopic Retrograde Cholangiopancreatography for the Management of Biliary Tract Disease after Roux-en-Y Gastric Bypass Treatment for Obesity

Abstract: Roux-en-Y gastric bypass (RYGB) is an effective treatment for morbid obesity. However, it may lead to diseases of the bilio-pancreatic tract. We evaluated transgastric endoscopic retrograde cholangiopancreatography (ERCP) for managing common biliary tract diseases in patients that underwent RYGB treatment for obesity. This prospective study was conducted between 2003 and 2010 at three medical institutions. We included 23 patients with a mean body mass index of 28.2 kg/m(2) after RYGB treatment. ERCP was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 17 publications
3
35
0
1
Order By: Relevance
“…In our study we found 5.8 % of sleeve patients and 6.4 % of LRYGB patients, already had their gallbladder removed or had gallstone disease before the operation. This result is similar to that of other studies (16,18). Portenier et al (14) argued that the incidence of delayed cholecystectomy for symptoms or complications of gallstone formation was much lower than the ≥30% reported to develop gallstones and suggested an expectant approach of the asymptomatic cholelithiasis in LRYGB patients.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…In our study we found 5.8 % of sleeve patients and 6.4 % of LRYGB patients, already had their gallbladder removed or had gallstone disease before the operation. This result is similar to that of other studies (16,18). Portenier et al (14) argued that the incidence of delayed cholecystectomy for symptoms or complications of gallstone formation was much lower than the ≥30% reported to develop gallstones and suggested an expectant approach of the asymptomatic cholelithiasis in LRYGB patients.…”
supporting
confidence: 88%
“…However, routine preoperative ultrasound screening for gallstones and/or prophylactic cholecystectomy may still be beneficial in LRYGB patients, because access to the biliary tract after LRYGB is challenging (18). In addition, positive gallstones in workups may interfere with diagnosing other reasons when the symptoms are not specific.…”
mentioning
confidence: 99%
“…Case series described in the literature point to success rates up to 100.0%, with complication rates similar to the traditional procedure [10,[43][44][45][46][47], demonstrating that it is technically superior to those using long frontal vision devices.…”
Section: Discussionmentioning
confidence: 99%
“…2017;7(4):58-63 the surgical team throughout the procedure are important factors that limit the diffusion of the use of this technique [10,[43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation